Developing Ways to Improve Traffic Management on Gayi Avenue - Sargsyan, A. T. (ՀԱԱՀ հիմնադրամ)
The article considers the ways of road traffic improvement through the coordinated management system on Gayi Avenue. The system has been designed to reduce traffic delays, which could entail to positive results, suh as optimal speed, increased safety, reduced environmental pollution, traffic jam reduction, etc. As a result of the current research it has become obvious that there is an urgent need to implement an automated traffic control system in order to organize safe traffic in the main streets of Yerevan.
Keywords: Agricultural Engineering